Iconicity in the lab: a review of behavioral, developmental, and neuroimaging research into sound-symbolism - Lockwood, Gwilym; Dingemanse, Mark (Frontiers in Psychology, 2015)
This review covers experimental approaches to sound-symbolism — from infants to adults, and from Sapir's foundational studies to 21st century product naming. It synthesises recent behavioural, developmental, and neuroimaging work into a systematic overview of the cross-modal correspondences that underpin iconic links between form and meaning. It also identifies open questions and opportunities, showing how the future course of experimental iconicity research can benefit from an integrated interdisciplinary perspective. Combining insights from psychology and neuroscience with evidence from natural languages provides us with opportunities for the experimental investigation of the role of sound-symbolism in language learning, language processing, and communication. It describes how hypothesis-testing and model-building will help contribute to a cumulative science of sound-symbolism in human language.